CHALLENGES FACING CONSTRUCTION CONTRACTS IN IRAQ - Sultan Noori Al-karawi (Journal of Engineering and Sustainable Development, 2018)
This paper aims at exploring the most important challenges which are facing the construction contracts in Iraq, and trying to analyze these challenges from various aspects. Addition, we have put necessary recommendations to support this sector through some notes and appropriate plans. Challenges are classified into eleven major problems (Political Problems, financial problems, administrative problems, problems related to the tender documents (contracts, drawings), problems related to the specifications and materials adaptation (Quality), problems related to the contract parties themselves, problems related to the sector environment, problems related to the natural environment, problems related to the arbitrations and disputes solving, problems related to the technology uses, problems related to the career ethics). These varieties have been agreed upon through questionnaire that was made for a number of the relevant authorities about the challenges facing them in construction sector. Each one of them contains a minor problems, it will be discussed such as (Rates burning due to intense competition between contractors.